ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI LIMAS DITINJAU DARI PERBEDAAN GENDER - Rizky Wahyudi; Hafriani; Darwani (Jurnal Anifa: Studi Gender dan Anak, 2023)
Mathematical problem-solving ability became one of the abilities that students must possess. However, based on the results of previous research, it was stated that there were differences between the abilities of male and female students in problem-solving abilities, so it required an in-depth understanding of mathematical problem-solving abilities based on gender. This study aims to determine the mathematical problem-solving abilities of junior high school students on pyramid material regarding gender differences. This research is qualitative research with a descriptive research type. The subjects in this study consisted of 6 students, consisting of 3 male and three female students, with high, medium and low students. Data were collected through written tests and interviews, then analyzed descriptively, including data reduction, data presentation and drawing conclusions. The results of the study were (1) female and male subjects in the high category fulfilled all indicators of problem-solving ability, but male subjects were less thorough than female subjects (2) female and male subjects in the medium category fulfilled three indicators of problem-solving ability problems, and made mistakes in making mathematical calculations, but male subjects made more mistakes than female subjects (3) Male and female subjects in the low category only met one indicator of problem-solving ability.